2021
DOI: 10.1136/jech-2020-216141
|View full text |Cite
|
Sign up to set email alerts
|

Trends in inequalities in disability in Europe between 2002 and 2017

Abstract: BackgroundMonitoring socioeconomic inequalities in population health is important in order to reduce them. We aim to determine if educational inequalities in Global Activity Limitation Indicator (GALI) disability have changed between 2002 and 2017 in Europe (26 countries).MethodsWe used logistic regression to quantify the annual change in disability prevalence by education, as well as the annual change in prevalence difference and ratio, both for the pooled sample and each country, as reported in the European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Meanwhile, the social and health inequalities experienced by the disadvantaged accumulate over their life course [ 2 ]. Significant socioeconomic inequalities in both physical and mental health have been observed in the older populations in both developing and developed countries [ 3 5 ]. China is no exception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the social and health inequalities experienced by the disadvantaged accumulate over their life course [ 2 ]. Significant socioeconomic inequalities in both physical and mental health have been observed in the older populations in both developing and developed countries [ 3 5 ]. China is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature consistently reported low SES in people with disability as measured by the Global Activity Limitation Indicator (GALI) and the Activities of Daily Living (ADL). For example, the populations with a higher prevalence of disability often experience lower school attendance, higher unemployment rate, and lower income [ 3 , 4 , 6 8 ]. Their poor health status is likely to be exacerbated by poor knowledge and low affordability of health services.…”
Section: Introductionmentioning
confidence: 99%
“…This absent correlation disagrees with numerous previously published studies. 1,[9][10][11][12][13][14]24 However, some existing studies reported an association between absent mortality and anxiety and depression, 25 or psychological distress. 26 Although a link between psychological distress and cardiovascular mortality is well established, 12,[27][28][29] some studies suggested that psychological symptoms were only associated with cardiovascular events, but not with cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effect of declining social status on health is well known. 1,2 Despite numerous difficulties in obtaining exact estimates of socioeconomic status, social status is believed to be fairly constant in Mediterranean countries. 3 Several studies from Croatia suggest that isolated island communities may pertain higher levels of social homogeneity, reflected in both a generalized lack of health inequalities, 4,5 extending even on to mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Rubio Valverde et al 1 show us that inequalities in disabilities in Europe have not improved between 2002 and 2017. They included a wide age range (30-79 years) and 26 countries.…”
Section: Elizabeth Breezementioning
confidence: 98%